Synthesis of N-zeolite and chabazite from kaolinite and bentonite - Claudia Belviso; Antonio Lettino; Luca Peruzzo; Francesco Cavalcante (Applied Clay Science, 2026)

First subsurface characterization of periglacial areas in the Yendegaia National Park, Southern Tierra del Fuego Island, Chile - Alberto Carrera; Mirko Pavoni; Sebastian Ruiz-Pereira; Jacopo Boaga; Luca Peruzzo; Viola Cioffi; Pawel Michal Slupski; Carlos Marquardt; Levente Ivan; Gergely Boros; Zoltan Szalai; Balazs Nagy (Cold Regions Science and Technology, 2026)

Trees control hillslope subsurface flow: Insights from stemflow and throughfall experiments, geophysical surveys, and numerical modeling - Simone Di Prima; Gersende Fernandes; Maria Burguet; Maria Paz Salazar; Elisa Marras; Ilenia Murgia; Konstantinos Kaffas; Luca Peruzzo; Ryan D. Stewart; Majdi R. Abou Najm; Alessandro Comegna; Laurent Lassabatere; et al. (Journal of Hydrology, 2026)

Sediment water storage investigation of check dams using electrical resistivity tomography - Sara Pini; Giorgio Cassiani; Luca Peruzzo; Luigi Piemontese; Andrea Dani; Yamuna Giambastiani; Federico Preti (Journal of Hydrology, 2026)

First thermographic survey within the Euganean thermal district (Italy) with an unmanned aerial vehicle - Luca Peruzzo; Andrea Berton; Michele Crivellaro; Cristina Da Lio; Sandra Donnici; Paolo Fabbri; Gian Marco Scarpa; Fabio Tateo; Luca Zaggia; Andrea Fasson (Remote Sensing Applications: Society and Environment, 2025)

Estimation of soil classes and their relationship to grapevine vigor in a Bordeaux vineyard: advancing the practical joint use of electromagnetic induction (EMI) and NDVI datasets for precision viticulture - Susan S. Hubbard; Myriam Schmutz; Abdoulaye Balde; Nicola Falco; Luca Peruzzo; Baptiste Dafflon; Emmanuel Léger; Yuxin Wu (Precision Agriculture, 2021)
Working within a vineyard in the Pessac Léognan Appellation of Bordeaux, France, this study documents the potential of using simple statistical methods with spatially-resolved and increasingly available electromagnetic induction (EMI) geophysical and normalized difference vegetation index (NDVI) datasets to accurately estimate Bordeaux vineyard soil classes and to quantitatively explore the relationship between vineyard soil types and grapevine vigor. First, co-located electrical tomographic tomography (ERT) and EMI datasets were compared to gain confidence about how the EMI method averaged soil properties over the grapevine rooting depth. Then, EMI data were used with core soil texture and soil-pit based interpretations of Bordeaux soil types (Brunisol, Redoxisol, Colluviosol and Calcosol) to estimate the spatial distribution of geophysically-identified Bordeaux soil classes. A strong relationship (r = 0.75, p < 0.01) was revealed between the geophysically-identified Bordeaux soil classes and NDVI (both 2 m resolution), showing that the highest grapevine vigor was associated with the Bordeaux soil classes having the largest clay fraction. The results suggest that within-block variability of grapevine vigor was largely controlled by variability in soil classes, and that carefully collected EMI and NDVI datasets can be exceedingly helpful for providing quantitative estimates of vineyard soil and vigor variability, as well as their covariation. The method is expected to be transferable to other viticultural regions, providing an approach to use easy-to-acquire, high resolution datasets to guide viticultural practices, including routine management and replanting.

Imaging of plant current pathways for non-invasive root Phenotyping using a newly developed electrical current source density approach - Luca Peruzzo; Chunwei Chou; Yuxin Wu; Myriam Schmutz; Benjamin Mary; Florian M. Wagner; Petr Petrov; Gregory Newman; Elison B. Blancaflor; Xiuwei Liu; Xuefeng Ma; Susan Hubbard (Plant and Soil, 2020)
Aims The flow of electric current in the root-soil system relates to the pathways of water and solutes, its characterization provides information on the root architecture and functioning. We developed a current source density approach with the goal of non-invasively image the current pathways in the root-soil system. Methods A current flow is applied from the plant stem to the soil, the proposed geoelectrical approach images the resulting distribution and intensity of the electric current in the root-soil system. The numerical inversion procedure underlying the approach was tested in numerical simulations and laboratory experiments with artificial metallic roots. We validated the method using rhizotron laboratory experiments on maize and cotton plants. Results Results from numerical and laboratory tests showed that our inversion approach was capable of imaging root-like distributions of the current source. In maize and cotton, roots acted as “leaky conductors”, resulting in successful imaging of the root crowns and negligible contribution of distal roots to the current flow. In contrast, the electrical insulating behavior of the cotton stems in dry soil supports the hypothesis that suberin layers can affect the mobility of ions and water. Conclusions The proposed approach with rhizotrons studies provides the first direct and concurrent characterization of the root-soil current pathways and their relationship with root functioning and architecture. This approach fills a major gap toward non-destructive imaging of roots in their natural soil environment.

A multi-metric registration strategy for the alignment of longitudinal brain images in pediatric oncology - Eros Montin; Antonella Belfatto; Marco Bologna; Silvia Meroni; Claudia Cavatorta; Emilia Pecori; Barbara Diletto; Maura Massimino; Maria Chiara Oprandi; Geraldina Poggi; Filippo Arrigoni; Denis Peruzzo; et al. (Medical & Biological Engineering & Computing, 2020)

Unraveling the Schneeberg garnet puzzle: a numerical model of multiple nucleation and coalescence - Harvey T. Dobbs; Luca Peruzzo; Flavio Seno; Richard Spiess; David J. Prior (Contributions to Mineralogy and Petrology, 2003)